Nanocrystalline and amorphous high-strength nickel-titanium alloy and preparation method thereof
Through multi-process coupling treatment of hot rotary forging, strong plastic deformation and aging treatment, high-strength nickel-titanium alloys with nanocrystalline amorphous were prepared, which solved the problem of insufficient tensile strength of existing nickel-titanium alloys, achieved the improvement of high strength and high elastic modulus, and met the need for miniaturization of medical devices.
Patent Information
- Application Number
- CN202411654887.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-03-14
AI Technical Summary
The existing ultra-elastic nickel-titanium wire or pipe have low tensile strength and cannot meet the needs of miniaturization of medical devices.
Through multi-process coupling treatment of hot rotary forging, strong plastic deformation and aging treatment, high-strength nickel-titanium alloys with nanocrystalline amorphous were prepared. Specific steps include: hot rotary forging to form an isometric ultrafine grain structure, then undergoing strong plastic deformation to obtain an amorphous phase, and then coexisting amorphous and nanocrystals through aging treatment.
Without losing elongation, the tensile strength and elastic modulus of nickel-titanium alloy are significantly improved, meeting the high strength and high elasticity characteristics required for the miniaturization of medical devices.
Smart Images

Figure CN119615031A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of nickel-titanium alloy manufacturing, and more specifically, to a nanocrystalline amorphous high-strength nickel-titanium alloy and a preparation method thereof. Background Art
[0002] Superelastic nickel-titanium wires or tubes have become one of the most important medical metal materials and have been widely used in various minimally invasive surgical medical devices, such as guidewires for catheters, stents, and filters. One of the development trends of medical devices is miniaturization, which is manifested in the development of neurovascular stents with small diameters and thin supports. Further miniaturization of medical devices requires smaller superelastic materials, such as microfilaments or thin-walled tubes, and the strength and rigidity of these materials need to be improved to meet the requirements of use.
[0003] The tensile strength of the currently available superelastic nickel-titanium wires or tubes is low and cannot meet the needs of miniaturization of medical devices. Summary of the invention
[0004] The purpose of the present invention is to overcome the above-mentioned defects of the prior art, provide a high-strength nickel-titanium alloy with nanocrystalline amorphous and a preparation method thereof, improve the tensile strength and elastic modulus of superelastic nickel-titanium wire or tube, while maintaining a comparable elongation.
[0005] To achieve the above object, the technical solution of the present invention is as follows:
[0006] In one aspect, the present invention provides a method for preparing a nanocrystalline amorphous high-strength nickel-titanium alloy, comprising the following steps:
[0007] S1, hot rotary forging a nickel-titanium alloy rod substrate to obtain an equiaxed ultrafine-grained nickel-titanium alloy substrate;
[0008] S2, subjecting the equiaxed ultrafine-grained nickel-titanium alloy matrix to a strong plastic deformation process to obtain an amorphous nickel-titanium alloy;
[0009] S3, subjecting the amorphous nickel-titanium alloy to aging treatment to obtain a nickel-titanium alloy in which an amorphous phase and nanocrystals coexist.
[0010] Optionally, the equiaxed ultrafine-grained nickel-titanium alloy substrate includes a plate, a cylinder, a tube or a wire.
[0011] Optionally, the temperature of the hot forging is higher than 600°C.
[0012] Optionally, the deformation amount of the hot rotary forging is greater than 50%.
[0013] Optionally, the severe plastic deformation process includes one or more of cold rolling, equal channel extrusion, cold drawing, and high pressure torsion.
[0014] Optionally, the intense plastic deformation process is cold rolling; and the deformation amount of each pass in the cold rolling process is less than or equal to 20%.
[0015] Optionally, the cold rolling includes multiple rolling deformations, so that the deformation of the equiaxed ultrafine grain nickel-titanium alloy is greater than 50%.
[0016] Optionally, the temperature of the aging treatment is 200°C-400°C.
[0017] Optionally, the aging treatment time is 0.5h-24h.
[0018] In another aspect, the present invention provides a high-strength nickel-titanium alloy having nanocrystalline amorphous properties, which is prepared by the above-mentioned method for preparing the high-strength nickel-titanium alloy having nanocrystalline amorphous properties.
[0019] Implementing the embodiments of the present invention will have the following beneficial effects:
[0020] The method for preparing a high-strength nickel-titanium alloy with nanocrystalline and amorphous materials provided in an embodiment of the present invention performs a multi-process coupling treatment of hot rotary forging-strong plastic deformation-aging treatment on the nickel-titanium alloy. After hot rotary forging to obtain an equiaxed ultrafine grain structure, strong plastic deformation is performed, the structure is fully crushed to obtain an amorphous phase, and finally aging treatment is performed to obtain a nickel-titanium alloy in which amorphous and nanocrystalline coexist, and high strength and high elastic modulus are obtained without losing elongation. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0022] in:
[0023] Figure 1 The present invention provides a flow chart of a method for preparing a nanocrystalline amorphous high-strength nickel-titanium alloy. DETAILED DESCRIPTION
[0024] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0025] Reference Figure 1The present invention discloses a method for preparing a nanocrystalline amorphous high-strength nickel-titanium alloy, comprising the following steps:
[0026] S1, hot rotary forging a nickel-titanium alloy rod substrate to obtain an equiaxed ultrafine-grained nickel-titanium alloy substrate;
[0027] Specifically, the ultrafine-grained nickel-titanium alloy matrix includes a plate, a cylinder, a tube or a wire. The size of the nickel-titanium alloy rod matrix is 2 mm-20 mm.
[0028] Furthermore, the temperature of hot rotary forging is higher than 600°C; the temperature of hot rotary forging can be 600°C, 650°C, 700°C, 750°C, 800°C, 850°C, 890°C or 900°C, and the temperature of hot rotary forging can also be any value within the above range, which is not specifically limited here.
[0029] Furthermore, the deformation amount of hot rotary forging is greater than 50%; the deformation amount of hot rotary forging can be 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85% or 90%, and the deformation amount of hot rotary forging can also be any value within the above range, which is not specifically limited here.
[0030] In this embodiment, the nickel-titanium rod matrix undergoes dynamic recrystallization in thermoplasticity through a hot rotary forging process to form an equiaxed ultrafine grain structure. Under thermoplastic deformation conditions, dynamic softening and work hardening of the alloy material compete with each other. When the dynamic softening effect and the work hardening effect reach a balance, the alloy is in a steady rheological state. When the processing temperature is higher than 600°C, the dynamic softening rate is greater than the work hardening rate. At this time, dynamic recrystallization is the main softening mechanism. Its grain nucleation and growth consume a large number of dislocations, resulting in a rapid decrease in rheological stress. At the same time, when the deformation is greater than 50%, the energy generated by the deformation is large enough to increase the dislocation density of the organization, aggravate the lattice distortion, increase the number of nuclei per unit volume, and significantly increase the number of dynamically recrystallized grains. When the work hardening rate is close to the dynamic softening rate, the dislocation density remains almost constant, so that the alloy is in a steady rheological state, forming equiaxed and fine grains.
[0031] When the temperature of hot forging is less than 600℃, the alloy takes dynamic recovery as the main softening mechanism. Dynamic recovery reduces the dislocation density by vacancy diffusion and mutual cancellation of dislocations of opposite signs, and dynamic recrystallization will not occur. When the deformation of hot forging is less than 50%, the driving force required for the nucleation of dynamic recrystallization grains in the alloy is insufficient, and dynamic crystallization will not occur.
[0032] S2, subjecting the equiaxed ultrafine-grained nickel-titanium alloy matrix to a strong plastic deformation process to obtain an amorphous nickel-titanium alloy;
[0033] Specifically, the severe plastic deformation process includes one or more of cold rolling, equal channel extrusion, cold drawing or high pressure torsion.
[0034] When the nickel-titanium alloy matrix is subjected to strong plastic deformation, microscopic mechanisms such as martensitic transformation, deformation twinning and dislocation slip can be induced. Under the action of these microscopic mechanisms, the lattice structure of the nickel-titanium alloy is gradually disrupted to form a disordered amorphous phase. Amorphous nickel-titanium alloy has properties such as high strength, high hardness, excellent corrosion resistance and biocompatibility.
[0035] Furthermore, the amorphous nickel-titanium alloy is prepared by a strong plastic deformation cold rolling process, in which the deformation of each pass is less than or equal to 20%, and multiple rolling deformations are performed, so that the deformation of the equiaxed ultrafine-grained nickel-titanium alloy is finally greater than 50% and there are no obvious microcracks on the surface.
[0036] S3. Performing aging treatment on the amorphous nickel-titanium alloy to obtain a nickel-titanium alloy in which the amorphous phase and nanocrystals coexist.
[0037] After intense plastic deformation to obtain amorphous nickel-titanium alloy, aging treatment is performed to further obtain a nickel-titanium alloy in which amorphous phase and nanocrystalline coexist. The amorphous phase usually has higher hardness and strength, while the nanocrystalline phase has good plasticity and toughness. This combination of microstructures allows the nickel-titanium alloy to have certain plasticity and toughness while maintaining high strength and hardness, thereby improving the comprehensive mechanical properties of the material.
[0038] The specific parameters of aging treatment such as temperature, time and cooling method have an important influence on the microstructure and mechanical properties of the final nickel-titanium alloy.
[0039] Furthermore, the aging treatment temperature is 200°C-400°C, the time is 0.5h-24h, and water cooling is adopted. When the aging treatment temperature is too high, the influence of dislocation and defect will disappear, the grain size will increase significantly, and the tensile strength will decrease significantly.
[0040] It can be understood that the preparation method of high-strength nickel-titanium alloy with nanocrystalline amorphous provided by the present invention is to perform hot rotary forging-strong plastic deformation-aging treatment on the nickel-titanium alloy. After hot rotary forging to obtain an equiaxed ultrafine grain structure, strong plastic deformation is performed, the structure is fully crushed to obtain an amorphous phase, and finally aging treatment is performed to obtain a nickel-titanium alloy in which amorphous and nanocrystalline coexist, and high strength and high elastic modulus are obtained without losing elongation. The processing method is simple and easy to operate, and meets the needs of industrial mass production.
[0041] The invention discloses a nickel-titanium alloy, which is prepared by any of the above-mentioned methods for preparing the high-strength nickel-titanium alloy with nanocrystalline amorphous properties. Specific embodiment:
[0043] Embodiment 1:
[0044] This embodiment provides a method for preparing a nanocrystalline amorphous high-strength nickel-titanium alloy, comprising the following steps:
[0045] S1. Hot rotary forging is performed on a nickel-titanium alloy rod with a diameter of 8.5 mm at a temperature of 900° C. and a deformation amount of 85% to obtain a nickel-titanium rod blank with a diameter of 3.29 mm.
[0046] S2. The obtained nickel-titanium rod blank with a diameter of 3.29 mm is cold-rolled, with a deformation amount of 10% in each pass and a total deformation amount of 55%, to obtain a nickel-titanium wire with a diameter of 2.2 mm.
[0047] S3. The obtained nickel-titanium wire with a diameter of 2.2 mm was subjected to aging treatment at a temperature of 400° C. for 5 h to obtain a nickel-titanium wire with high strength and high elastic modulus.
[0048] Embodiment 2:
[0049] This embodiment provides a method for preparing a nanocrystalline amorphous high-strength nickel-titanium alloy, comprising the following steps:
[0050] S1. Hot rotary forging is performed on a nickel-titanium alloy rod with a diameter of 6.0 mm at a temperature of 800° C. and a deformation amount of 75% to obtain a nickel-titanium rod with a diameter of 3.0 mm.
[0051] S2. The obtained nickel-titanium rod with a diameter of 3.0 mm is cold drawn, with a deformation amount of 12% in each pass and a total deformation amount of 70%, to obtain a nickel-titanium wire with a diameter of 1.64 mm.
[0052] S3. The obtained nickel-titanium wire with a diameter of 1.64 mm was subjected to aging treatment at a temperature of 300° C. for 3 h to obtain a nickel-titanium wire with high strength and high elastic modulus.
[0053] Example 3
[0054] This embodiment provides a method for preparing a nanocrystalline amorphous high-strength nickel-titanium alloy, comprising the following steps:
[0055] S1. Hot rotary forging is performed on a nickel-titanium alloy rod with a diameter of 2.5 mm at a temperature of 720° C. and a deformation amount of 70% to obtain a nickel-titanium rod with a diameter of 1.37 mm.
[0056] S2. The obtained nickel-titanium rod with a diameter of 1.37 mm is cold drawn, with a deformation amount of 15% in each pass and a total deformation amount of 80%, to obtain a nickel-titanium wire with a diameter of 0.61 mm.
[0057] S3. The obtained nickel-titanium wire with a diameter of 0.61 mm was subjected to aging treatment at a temperature of 220° C. for 2 h to obtain a nickel-titanium wire with high strength and high elastic modulus.
[0058] Comparative Example 1:
[0059] S1. A nickel-titanium alloy rod with a diameter of 8.5 mm was hot drawn at a temperature of 900°C and a deformation of 85%. The rod blank cracked and the finished product could not be obtained.
[0060] Comparative Example 2:
[0061] S1. Hot rotary forging is performed on a nickel-titanium alloy rod with a diameter of 8.5 mm at a temperature of 900° C. and a deformation amount of 85% to obtain a nickel-titanium rod blank with a diameter of 3.29 mm.
[0062] S2. The obtained nickel-titanium rod blank with a diameter of 3.29 mm is subjected to hot drawing at a temperature of 700° C., with a deformation amount of 10% in each pass and a total deformation amount of 55%, to obtain a nickel-titanium wire with a diameter of 2.2 mm.
[0063] S3. Perform aging treatment on the obtained nickel-titanium wire with a diameter of 2.2 mm at a temperature of 400° C. for 5 h to obtain nickel-titanium wire.
[0064] Comparative Example 3:
[0065] S1. Hot rotary forging is performed on a nickel-titanium alloy rod with a diameter of 8.5 mm at a temperature of 900° C. and a deformation amount of 85% to obtain a nickel-titanium rod blank with a diameter of 3.29 mm.
[0066] S2. The obtained nickel-titanium rod blank with a diameter of 3.29 mm is cold-rolled, with a deformation amount of 10% in each pass and a total deformation amount of 55%, to obtain a nickel-titanium wire with a diameter of 2.2 mm.
[0067] Table 1 Performance test results of nickel-titanium alloys obtained in Examples 1-3 and Comparative Examples 1-3
[0068]
[0069] In step S1 of comparative example 1, hot rotary forging was not used, but hot drawing was used. When the deformation amount reached 85%, the rod blank cracked and the finished product could not be obtained. In step S2 of comparative example 1, a strong plastic deformation process was not used, but hot drawing was used. The tensile strength and elastic modulus of the finished product were significantly lower than those of Example 1. In comparative example 3, aging treatment was not used, and the tensile strength and elastic modulus of the finished product were significantly lower than those of Example 1.
[0070] Comparative Example 4:
[0071] S1. Hot rotary forging is performed on a nickel-titanium alloy rod with a diameter of 8.5 mm at a temperature of 900° C. and a deformation amount of 40% to obtain a nickel-titanium rod blank with a diameter of 6.58 mm.
[0072] S2. The obtained nickel-titanium rod blank with a diameter of 6.58 mm is cold-rolled, with a deformation amount of 10% in each pass and a total deformation amount of 55%, to obtain a nickel-titanium wire with a diameter of 4.41 mm.
[0073] S3. Perform aging treatment on the obtained nickel-titanium wire with a diameter of 4.41 mm at a temperature of 400° C. for 5 h to obtain nickel-titanium wire.
[0074] Comparative Example 5:
[0075] S1. Hot rotary forging was performed on a nickel-titanium alloy bar with a diameter of 8.5 mm at a temperature of 500°C and a deformation of 85%. The bar blank cracked and the finished product could not be obtained.
[0076] Table 2 Performance test results of nickel-titanium alloy obtained in Example 4 and Comparative Examples 4 and 5
[0077]
[0078] In comparative example 4, the hot forging deformation in step S1 is less than 50%, and the hot forging deformation is 40%. The tensile strength and elastic modulus of the finished product are significantly lower than those in embodiment 1. In comparative example 5, the hot forging temperature in step S1 is less than 600°C, and the hot forging temperature is 500°C. When the deformation reaches 85%, the rod blank cracks and the finished product cannot be obtained.
[0079] Comparative Example 6:
[0080] The total deformation amount of cold rolling in step S2 of comparative example 6 is 35%, and the other steps are the same as those of embodiment 1.
[0081] Comparative Example 7:
[0082] The temperature of the aging treatment in step S3 of comparative example 7 is 100° C., and the other steps are the same as those of example 1.
[0083] Comparative Example 8:
[0084] The temperature of the aging treatment in step S3 of comparative example 8 is 550° C., and the other steps are the same as those of example 1.
[0085] Table 3 Performance test results of nickel-titanium alloys obtained in Example 1 and Comparative Examples 6-8
[0086] Sample specifications Tensile strength / MPa Uniform strain / % Elastic modulus / GPa Example 1 Diameter 2.20mm 2115 5.9 69 Example 6 Diameter 2.65mm 1791 4.8 62 Example 7 Diameter 2.20mm 1917 4.5 61 Comparative Example 8 Diameter 2.20mm 1352 13.7 58
[0087] In comparative example 6, the cold rolling deformation amount in step S2 is less than 50%, and the cold rolling deformation amount is 35%, and the tensile strength and elastic modulus of the finished product are significantly lower than those in Example 1; in comparative example 7, the aging treatment temperature in step S3 is lower than 200°C, and the aging treatment temperature is 100°C, and the tensile strength and elastic modulus of the finished product are lower than those in Example 1; in comparative example 8, the aging treatment temperature in step S3 is higher than 400°C, and the aging treatment is 550°C, and the tensile strength and elastic modulus of the finished product are significantly lower than those in Example 1.
[0088] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent application. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A method for preparing a nanocrystalline amorphous high-strength nickel-titanium alloy, characterized in that: The process includes: S1, hot rotary forging a nickel-titanium alloy rod substrate to obtain an equiaxed ultrafine-grained nickel-titanium alloy substrate; S2, subjecting the equiaxed ultrafine-grained nickel-titanium alloy matrix to a strong plastic deformation process to obtain an amorphous nickel-titanium alloy; S3, subjecting the amorphous nickel-titanium alloy to aging treatment to obtain a nickel-titanium alloy in which an amorphous phase and nanocrystals coexist.
2. The method for preparing a nanocrystalline amorphous high-strength nickel-titanium alloy according to claim 1, characterized in that: The equiaxed ultrafine-grained nickel-titanium alloy matrix includes a plate, a cylinder, a tube or a wire.
3. The method for preparing a nanocrystalline amorphous high-strength nickel-titanium alloy according to claim 1, characterized in that: The temperature of the hot rotary forging is higher than 600°C.
4. The method for preparing a nanocrystalline amorphous high-strength nickel-titanium alloy according to claim 1, characterized in that: The deformation amount of the hot rotary forging is greater than 50%.
5. The method for preparing a nanocrystalline amorphous high-strength nickel-titanium alloy according to claim 1, characterized in that: The severe plastic deformation process includes one or more of cold rolling, equal channel extrusion, cold drawing, and high pressure torsion.
6. The method for preparing a nanocrystalline amorphous high-strength nickel-titanium alloy according to claim 1, characterized in that: The intense plastic deformation process is cold rolling; the deformation amount of each pass in the cold rolling process is less than or equal to 20%.
7. The method for preparing a nanocrystalline amorphous high-strength nickel-titanium alloy according to claim 6, characterized in that: The cold rolling includes multiple rolling deformations, so that the deformation amount of the equiaxed ultrafine grain nickel-titanium alloy is greater than 50%.
8. The method for preparing a nanocrystalline amorphous high-strength nickel-titanium alloy according to claim 1, characterized in that: The temperature of the aging treatment is 200°C-400°C.
9. The method for preparing a nanocrystalline amorphous high-strength nickel-titanium alloy according to claim 1, characterized in that: The aging treatment time is 0.5h-24h.
10. A high-strength nickel-titanium alloy with nanocrystalline amorphous properties, characterized in that: The invention is prepared by the preparation method of the nanocrystalline amorphous high-strength nickel-titanium alloy according to any one of claims 1 to 9.